Impact of Macroeconomic Events on Shanghai Stock Exchange - Singhania, Keshav; G.P, Girish (Asian Journal of Empirical Research, 2015)
In this study we investigate the impact of macroeconomic events (i.e. 2000 dot-com bubble, 2008 Global financial crisis and 2015 announcement of RNB consideration in the SDR basket) on returns of Shanghai Stock Exchange Composite Index for 2000 dot com bubble (t ± 30 days as the event window), 2008 Global financial crisis (t ± 60 days as the event window) and 2015 stock market crash in China aided by announcement of RNB getting listed in the basket of currencies i.e. in SDR (t ± 60 days as the event window) by applying event study technique for quantifying Average Abnormal Returns and Cumulative Average Abnormal Returns and test for statistical significance of the obtained results. We find that the Returns of Shanghai Stock Exchange Composite Index responded negatively to the events implying that Chinese stock market was negatively affected by all three events considered but varying in the degree of their impact owing to the extent of impact on the economy of China as a whole. The results of the study provide insights to potential investors, fund managers and policymakers to take an informed decision whether to invest in Shanghai Stock Exchange if such events would reoccur in future.